Predictors Of Postoperative Lower Urinary Tract Symptoms Improvements In Patient With Small-Volume Prostate And Bladder Outlet Obstruction - Li XD; Wu YP; Ke ZB; Lin TT; Chen SH; Xue XY; Xu N; Wei Y (Dove Medical Press, 2019)
Xiao-Dong Li,* Yu-Peng Wu,* Zhi-Bin Ke,* Ting-Ting Lin,* Shao-Hao Chen, Xue-Yi Xue, Ning Xu, Yong Wei Departments of Urology, The First Affiliated Hospital of Fujian Medical University, Fuzhou 350005, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yong Wei; Ning XuDepartment of Urology, The First Affiliated Hospital of Fujian Medical University, 20 Chazhong Road, Fuzhou 350005, People’s Republic of ChinaTel +86 0591 8798 1687Email weiyong2017@fjmu.edu.cn; drxun@fjmu.edu.cnObjective: To explore the factors associated with improvement of lower urinary tract symptoms (LUTS) after transurethral plasmakinetic enucleation of the prostate (PKEP) and transurethral resection of the prostate (TURP) in patients with a small-volume prostate and bladder outlet obstruction (BOO).Methods: The clinicopathologic data of 257 patients with BOO and a small-volume prostate from January 2013 to January 2018 were retrospectively collected preoperatively, 3 months postoperatively, and 12 months postoperatively. Patients were divided into postoperative success and failure groups based on the IPSS, IPSS-v, and IPSS-s. The relationship between each parameter and the improvement of postoperative LUTS was analyzed. Subgroup analysis was performed to compare the differences between the TURP and PKEP groups.Results: Among patients followed up for 3 months postoperatively, multivariate analysis demonstrated that IPP, PUA, and post-PCB were significant predictors of postoperative IPSS improvement; TZI, IPP, and PUA were significant predictors of postoperative IPSS-v improvement; post-PCB and the surgical procedure were significant predictors of IPSS-s improvement; and IPP and PUA were significant predictors of postoperative Qmax improvement. Among patients followed up for 12 months postoperatively, multivariate analysis revealed that IPP, PUA, and post-PCB were significant predictors of postoperative IPSS improvement; PUA was a significant predictor of postoperative IPSS-v improvement; post-PCB was a significant predictor of IPSS-s improvement; and IPP and PUA were significant predictors of postoperative Qmax improvement. The post-PCB was significantly lower in the PKEP than the TURP group and the prostatic calculi removal rate was significantly higher in the PKEP than the TURP group.Conclusion: Patients with a greater preoperative IPP and PUA and smaller post-PCB showed greater improvement of postoperative LUTS. PKEP might help to remove calculi from between the transitional and peripheral zones of prostate. Compared with conventional TURP, PKEP may improve the early postoperative storage symptoms of LUTS in patients with a small-volume prostate and BOO.Keywords: small-volume prostate, lower urinary tract symptoms, International Prostate Symptom Score